Time to diagnosis and treatment for breast cancer in public and private health services - Angélica Atala Lombelo Campos; Maximiliano Ribeiro Guerra; Vívian Assis Fayer; Rafaela Russi Ervilha; Jane Rocha Duarte Cintra; Iara Renault de Medeiros; Matheus Calábria da Silveira; Maria Teresa Bustamante-Teixeira (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To analyze the time to diagnosis and treatment for breast cancer and the associated factors, according to the type of care (public vs. private). Methodology: Retrospective cohort study with 477 women diagnosed with breast cancer between 2014 and 2016. Data were collected in an oncology service in a municipality in Minas Gerais, in the 2018-2019 period. Analyzes were performed using the Kaplan-Meier method and Cox's proportional regression model. Results: The median time to diagnosis was 70 days, being shorter for women who discovered the disease through screening tests and who were diagnosed in early stages of the disease. The median time for treatment was 32 days, which was shorter for women assisted by private health service, with a high level of education and who were diagnosed in early stages. Conclusions: Private care and facilitators of access to breast cancer care were associated with shorter waiting times.